PENDAMPINGAN PENGGUNAAN REFERENCE MANAGER MENDELEY DENGAN GAYA “APA MANUAL 7TH EDITION” DALAM MENYUSUN KARYA ILMIAH - Mohammad Tohir; Ahmad Yunus; Ahmad Jazuly; Ianatuz Zahro; Ninuk Indrayani (As-Sidanah, 2022)
Students as prospective teachers are said to be professional educators if they have pedagogical competence, personality competence, social competence, and professional competence. In this training activity, the focus of the activity is on the professional competence of students as prospective teachers, namely the ability to master scientific writing with the help of software. Writing scientific papers that must be done is to include a bibliography. The number of references needed by students in writing scientific papers, therefore, some of them will find it difficult to make a bibliography manually. Therefore, the Mendeley application is needed to make it easier to compile a bibliography automatically. However, there are still many students who do not understand its use and do not even know the Mendeley application. This training is held offline in the classroom, with the target participants being students of IKIP PGRI Jember, especially S1 Early Childhood Education Programs (ECEG) final semester. The method used in this service activity is Participatory Action Research (PAR). The use of this method is expected to improve students' understanding and skills in compiling scientific papers related to citation arrangements, and bibliography. The subject of service according to the title is S1 Early Childhood Education Programs (ECEG) final semester. The object of training is the Mendeley Application with the "APA Manual 7th Edition" style which has been implemented at IKIP PGRI Jember.